أثر النشاط التسويقي في تحقيق الأداء التنافسي لشركات التأمين السورية - الخضر علي; الحسين رولا (Latakia University Journal - Economic and Legal Sciences Series, 2016)
هدفت الدراسة إلى بيان مدى تأثير تتبع مؤشرات أداء التسويقي في تحقيق أداء تنافسي كلي، وقد قامت الباحثة بتطبيق الدراسة على مجموعة من شركات التأمين العاملة في سورية حيث قامت بتوزيع /110/ استمارات على العاملين بها؛ وقد خلصت الدراسة إلى مجموعة من النتائج كان أهمها أنه يوجد تأثير معنوي للأداء التسويقي على الأداء التنافسي في الشركات محل الدراسة؛ كما وجدت الباحثة أنه توجد اختلافات جوهرية بين أفراد عينة الدراسة فيما يتعلق بالأداء التسويقي والأداء التنافسي بالنسبة للخبرة المهنية. The Study aimed to explore the potential effect of following marketing performance indicators in achieving competitive performance in general; though, the author applied the study on group of insurance companies in Syria through distributing /110/ questionnaires to their employees; the study conducted some results: there is a significant effect for the marketing performance on the competitive performance, and that there is significant differences between the questioned one about their view to the marketing performance and competitive performance according to the experience.